Photo-thermal evaporation-photocatalytic hydrogen production composite material as well as preparation method and application thereof

By forming a carbonized layer on decellulose-treated wood and coating it with NvCN photocatalyst, the problems of catalyst poisoning and light scattering in seawater photocatalytic hydrogen production were solved, the spectral absorption was broadened, the electron-hole separation was optimized, and the synergistic process of seawater desalination and hydrogen production was realized, thereby improving the utilization rate of light energy and the hydrogen production.

CN121372464APending Publication Date: 2026-01-23SHANDONG UNIV

Patent Information

Application Number
CN202511617826.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-06
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing photocatalytic water splitting technology for hydrogen production faces problems such as catalyst poisoning, salting out and blockage, and light scattering when using seawater. Furthermore, the energy in the infrared band is difficult to utilize, resulting in low conversion efficiency and making it difficult to achieve high utilization of solar energy.

Method used

Using decellulose-treated wood as the matrix, a carbonized layer is formed through carbonization treatment, and a nitrogen-vacant carbon nitride (NvCN) photocatalyst is coated on it to form a photothermal evaporation-photocatalytic hydrogen production composite material. Water vapor is used as the reaction raw material for photocatalytic hydrogen production, which broadens the spectral absorption to the visible and near-infrared regions and optimizes electron-hole separation and transfer.

Benefits of technology

This method enables the synergistic process of seawater desalination and hydrogen production, improves the utilization rate of light energy, enhances hydrogen production, avoids the accumulation of metal ions on the catalyst surface, reduces the probability of competitive reduction reactions, and improves the stability and efficiency of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121372464A_ABST
    Figure CN121372464A_ABST
Patent Text Reader

Abstract

According to the photo-thermal evaporation-photocatalysis hydrogen production system, hydrogen production can be carried out while seawater desalination is achieved through a photo-thermal evaporation-photocatalysis hydrogen production composite material, photo-thermal conversion can be achieved through carbonized wood (wood subjected to surface carbonization treatment), and seawater is evaporated to obtain water vapor; the water vapor participates in hydrogen production reaction on the surface of the photocatalytic hydrogen production catalyst as a reaction raw material. The photo-thermal evaporation-photocatalytic hydrogen production composite material provided by the invention not only can broaden spectral absorption, but also can expand the absorption wavelength of a sunlight spectrum to visible light and near-infrared regions; meanwhile, the interface reaction resistance is also reduced, and electron-hole separation and transfer are optimized, so that the utilization rate of light energy is improved, and the yield of hydrogen is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of photocatalysis, in particular to a photo-thermal evaporation-photocatalytic hydrogen production composite material and a preparation method and application thereof. BACKGROUND

[0002] The information disclosed in this Background section is only for the purpose of increasing an understanding of the general background of the application and does not necessarily constitute an admission or a recognition that the information forms part of the prior art that is already known in any country in the world.

[0003] Hydrogen has the characteristics of high energy density, easy storage and transportation, no carbon emission and renewable, making it one of the main representatives of clean energy. Using solar photocatalytic decomposition of water to produce hydrogen is one of the methods to realize pollution-free hydrogen production. The basic principle of photocatalytic decomposition of water to produce hydrogen is that the semiconductor photocatalyst generates photo-generated electron-hole pairs under the excitation of sunlight, and the electrons migrating to the surface of the photocatalyst reduce water to hydrogen, while the holes oxidize water to oxygen.

[0004] However, photocatalytic decomposition of water to produce hydrogen mainly relies on the decomposition of fresh water. Considering the shortage of global fresh water resources and the abundance of seawater, it is urgent to develop a photocatalytic hydrogen production system using seawater as a proton source. Existing research attempts to directly use seawater for photocatalytic hydrogen production, but the ions and impurities in water can cause catalyst poisoning, salt precipitation blockage and light scattering problems, making it difficult to meet the actual application requirements in terms of reaction activity and long-term stability. Therefore, water vapor generated by seawater desalination can be provided to the photocatalyst as a reaction raw material, because water vapor contains less ions and has a lower impact on the efficiency of the photocatalyst, and the corrosion ability of water vapor on the surface structure of the photocatalyst is much lower than that of seawater.

[0005] In addition, photocatalytic decomposition of water to produce hydrogen has strict requirements on the band gap of semiconductor materials. Most current photocatalysts can only utilize ultraviolet light and part of the visible light band in solar energy, while infrared light band is difficult to directly utilize and becomes heat dissipation, which makes the conversion efficiency of the photocatalyst low and the overall actual performance decreases, also indicating that it is difficult to achieve high utilization of solar energy through a single photocatalytic means. SUMMARY

[0006] In order to overcome the above problems, the present application provides a photo-thermal evaporation-photocatalytic hydrogen production composite material and a preparation method and application thereof.

[0007] In order to achieve the above technical purposes, the present application adopts the following technical solutions: In a first aspect, the present application provides a photo-thermal evaporation-photocatalytic hydrogen production composite material, which uses delignified wood as a matrix, performs carbonization treatment on the upper surface of the matrix to obtain a carbonized layer, and then coats a photocatalytic hydrogen production catalyst on the upper surface of the carbonized layer. The photocatalytic hydrogen production catalyst is a nitrogen vacancy-containing carbon nitride (NvCN) photocatalyst.

[0008] In one or more embodiments, the wood is pine wood.

[0009] In one or more embodiments, the thickness ratio of the carbonized layer is 5% to 15%.

[0010] In one or more embodiments, the loading amount of the photocatalytic hydrogen production catalyst is 2 to 6 mg / cm 2 , preferably 3.3 mg / cm 2 .

[0011] In one or more embodiments, the preparation method of the nitrogen vacancy-containing carbon nitride (NvCN) photocatalyst comprises the following steps: Dissolve urea and N-(4-cyanophenyl)-glycine in an ethanol aqueous solution, collect the solid after removing the solvent by evaporation to obtain a precursor; Heat treat the precursor to obtain the nitrogen vacancy-containing carbon nitride (NvCN) photocatalyst.

[0012] Preferably, the mass ratio of the urea and N-(4-cyanophenyl)-glycine is 10000: (1 to 7), preferably 10000:3.

[0013] Preferably, the volume ratio of ethanol to water in the ethanol aqueous solution is (4.5 to 5.5):1, preferably 5:1.

[0014] Preferably, the concentration of N-(4-cyanophenyl)-glycine in the ethanol aqueous solution is 0.3 to 2.3 g / L, preferably 1 g / L.

[0015] Preferably, the temperature for removing the solvent by evaporation is 75 to 85 ℃, preferably 80 ℃.

[0016] Preferably, the temperature for heat treatment is 500 to 600 ℃, preferably 550 ℃; the time for heat treatment is 1.5 to 2.5 h, preferably 2 h; and the heating rate is 4.5 to 5.5 ℃ / min, preferably 5 ℃ / min.

[0017] In a second aspect of the present application, a preparation method of the photo-thermal evaporation-photocatalytic hydrogen production composite material of the first aspect is provided, comprising the following steps: (1) immerse the wood in a 4-methylmorpholine N-oxide aqueous solution, and after taking out, wash and dry to obtain a cellulose-removed wood; (2) perform carbonization treatment on the upper surface of the cellulose-removed wood to obtain a carbonized layer, and then coat a photocatalytic hydrogen production catalyst on the upper surface of the carbonized layer; and after drying, obtain the photo-thermal evaporation-photocatalytic hydrogen production composite material.

[0018] In one or more embodiments, in step (1), the concentration of the aqueous 4-methylmorpholine N-oxide solution is 20-30 wt%, preferably 25 wt%.

[0019] In one or more embodiments, in step (1), the temperature for immersing in the aqueous 4-methylmorpholine N-oxide solution is 4-10 ℃, preferably 6 ℃; the time for immersing in the aqueous 4-methylmorpholine N-oxide solution is 2.5-4 h, preferably 3 h.

[0020] In one or more embodiments, in step (2), the method for carbonizing includes: placing the surface to be carbonized on a stainless steel plate, heating with an alcohol lamp, and then immersing in water for quenching.

[0021] Preferably, the time for heating is 10-20 min, preferably 15 min.

[0022] In one or more embodiments, in step (2), the method for coating the photocatalytic hydrogen production catalyst on the upper surface of the carbonized layer includes: dissolving polyvinylidene fluoride in N-methyl-2-pyrrolidone to obtain a mixed solution; dispersing the photocatalytic hydrogen production catalyst in the mixed solution, and then coating on the upper surface of the carbonized layer.

[0023] Preferably, in the mixed solution, the concentration of polyvinylidene fluoride is 25-35 g / L, preferably 30 g / L.

[0024] Preferably, the concentration of the photocatalytic hydrogen production catalyst is 8-12 g / L, preferably 10 g / L.

[0025] In a third aspect of the present application, the application of the photo-thermal evaporation-photocatalytic hydrogen production composite material of the first aspect or the photo-thermal evaporation-photocatalytic hydrogen production composite material prepared by the preparation method of the second aspect in photocatalytic seawater hydrogen production is provided.

[0026] In a fourth aspect of the present application, a method for seawater hydrogen production is provided, which includes the following steps: floating the photo-thermal evaporation-photocatalytic hydrogen production composite material on the surface of seawater, with the surface coated with the photocatalytic hydrogen production catalyst facing upwards, and producing hydrogen under light irradiation.

[0027] The present application has the following beneficial effects: (1) The present application provides a kind of photo-thermal evaporation-photocatalytic hydrogen production system, utilize the photo-thermal evaporation-photocatalytic hydrogen production composite material provided by the present application can realize seawater desalination while producing hydrogen, wherein carbonized wood (surface carbonization treated wood) can realize photo-thermal conversion, evaporate seawater to obtain water vapor;Water vapor as raw material on the surface of photocatalytic hydrogen production catalyst participates in hydrogen production reaction.The photo-thermal evaporation-photocatalytic hydrogen production composite material provided by the present application not only can widen the spectrum absorption, extend the absorption wavelength of solar spectrum to visible light and near infrared region;It also reduces the interface reaction resistance, and optimizes the separation and transfer of electron-hole, thereby improves the light energy utilization, and then improves the hydrogen production.

[0028] (2) Because the metal ions in seawater lose the carrier in the vaporization process, and no longer migrate to the surface of the catalyst with water vapor, therefore, the accumulation and coverage of metal ions on the catalyst are effectively avoided, and the active sites are prevented from being shielded and the loss of photo-generated carriers is prevented.At the same time, the gaseous environment reduces the contact opportunity of metal ions and H + , significantly reduces the probability of occurrence of competitive reduction reaction.

[0029] (3) The gas-solid interface formed by water vapor-photocatalytic hydrogen production catalyst effectively reduces the hydrogen desorption and mass transfer resistance, and the low standard free energy of gaseous water vapor reduces the reaction threshold of photocatalytic hydrogen production.These synergies make the hydrogen production rate in seawater environment significantly exceed the traditional powder system, and maintain excellent stability. BRIEF DESCRIPTION OF DRAWINGS

[0030] The drawings accompanying the specification of the present application form a part thereof, serve to further understand the present application, and the illustrative embodiments of the present application and their descriptions serve to explain the present application, and do not constitute an improper limitation on the present application.

[0031] Figure 1 The device for hydrogen production test of photo-thermal evaporation-photocatalytic hydrogen production composite material; Figure 2 The preparation method of photo-thermal evaporation-photocatalytic hydrogen production composite material; Figure 3 (a) is the original untreated natural wood, (b) is carbonized wood, (c) is the water contact angle of NvCN-CW, and (d) is the schematic diagram of hydrophilicity and hydrophobicity of each part after synthesis; Figure 4(a) is a scanning electron microscope image of the original untreated natural wood, (b) is a scanning electron microscope image of the pretreated wood; (c) is a front view scanning electron microscope image of NvCN-CW, (d) is an EDS mapping image of C, N, O, and F elements in NvCN-CW, (e) is a side view scanning electron microscope image of NvCN-CW, (f) is a scanning electron microscope image of the surface pore edge of NvCN-CW (5-hole); Figure 5 is the UV-Vis diffuse reflectance spectra of the solar spectrum and NvCN-CW and NvCN; Figure 6 is the photocatalytic hydrogen production amount of pure CW; Figure 7 (a) is the hydrogen production rate of NvCN-CW with different mass loadings; (b) is the photocatalytic hydrogen production rate of NvCN-CW, NvCN-W, and NvCN; (c) is the cycling experiment of NvCN-CW; (d) is the photocatalytic hydrogen production of NvCN-CW under different wavelengths; Figure 8 is the hydrogen production rate of NvCN-CW with and without light; Figure 9 (a) is the potential of water splitting under different conditions, (b) is the photocatalytic hydrogen evolution in different photocatalyst systems; Figure 10 (a) is the hydrogen production rate of NvCN-CW at 25 °C and 60 °C; (b) is the electrochemical impedance spectroscopy of the original untreated natural wood, carbonized wood, and NvCN-CW; (c) is the transient photocurrent curve of NvCN-CW and NvCN-W; (d) is the hydrogen production rate of NvCN-CW under different water sources; Figure 11 is the evaporation rate of NvCN-CW with different mass loadings; Figure 12 (a) is the hydrogen production rate of NvCN-CW and its different pore structures (5-hole, 9-hole, 13-hole); (b) is the evaporation rate of NvCN-CW and its different pore structures (5-hole, 9-hole, 13-hole); (c) is the infrared imaging temperature distribution of NvCN-CW and its different pore structures (5-hole, 9-hole, 13-hole) under solar irradiation; Figure 13 (a) is the water evaporation mass change and (b) is the water evaporation rate of NvCN-CW, CW, and pure water; (c) is the water evaporation rate of the original untreated natural wood, cellulose-removed wood, and CW; (d) is the water evaporation rate of NvCN-CW under different water sources; Figure 14 is the water evaporation rate of the original untreated natural wood, cellulose-removed wood, and CW; Figure 15 The evaporation rate of NvCN-CW under light and dark conditions; Figure 16 Fourier transform infrared (FTIR) spectrum; Figure 17 The process of photothermal evaporation-photocatalytic hydrogen production for NvCN-CW. Detailed Implementation

[0032] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0033] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0034] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0035] use Figure 1 The apparatus shown was used for hydrogen production testing: the photocatalytic hydrogen production evaluation was conducted in a closed reactor with a volume of 200 mL, using a 300 W xenon lamp as the light source. In the photocatalytic hydrogen production evaluation, 1.0 wt% platinum was deposited on the surface of the photocatalytic hydrogen production catalyst using surface photodeposition to form an integrated NvCN / CW photocatalyst. The reaction system consisted of the monolithic NvCN / CW photocatalyst and 100 mL of triethanolamine (10% by volume) aqueous solution; air in the reactor was purged by introducing argon gas; a cooling water system was used during the hydrogen production process to ensure the water body maintained a constant temperature and to avoid the influence of room temperature on evaporation; the light source was turned on to initiate the photochemical process; during the 6-hour test, 100 μL of gas was extracted from the reactor every 2 hours and injected into a gas chromatograph to detect the hydrogen production.

[0036] For comparison, the photocatalytic hydrogen production of NvCN was also evaluated. 30 mg of the catalyst was dispersed in 100 mL of a 10% (v / v) aqueous solution of triethanolamine, with other conditions remaining the same as described above. Furthermore, the photocatalytic hydrogen production performance of different reaction systems was investigated, including an NvCN powder system at 60 °C and an NvCN / W monolithic photocatalyst system.

[0037] Steam generation measurement: The evaporation performance of water was measured under the irradiation of a 300 W xenon lamp equipped with an AM 1.5G optical filter (100 mW cm -2 The evaporation performance of water was measured under the irradiation of a 300 W xenon lamp equipped with an AM 1.5G optical filter (100 mW cm

[0038] Example 1 Figure 2 For the preparation method of the photo-thermal evaporation-photocatalytic hydrogen production composite material, refer to Figure 2 The photo-thermal evaporation-photocatalytic hydrogen production composite material is prepared.

[0039] (1) Synthesis of surface carbonized wood (CW): Pine wood was cut into a cuboid with a size of 3 cm x 3 cm x 1 cm; the pine wood was immersed in a 25 wt% aqueous solution of 4-methylmorpholine N-oxide, soaked at 6 °C for 3 h to dissolve cellulose and thus expand the pores. The treated wood was washed with deionized water under ultrasonic conditions for 1 h, and the washing was repeated 3 times. The washed wood was placed in a vacuum oven and dried at 60 °C for 12 h to obtain pretreated wood (W).

[0040] The pretreated wood was placed on a flat stainless steel plate and heated with an alcohol lamp for 15 min. Then, the wood was immediately immersed in water for rapid quenching; a single-sided carbonized wood was obtained, denoted as carbonized wood (CW).

[0041] (2) Preparation of nitrogen vacancy-containing carbon nitride (NvCN) photocatalyst: 10 g of urea and 3 mg of N-(4-cyanophenyl)-glycine were dispersed in a mixed solvent consisting of 5 mL of deionized water and 25 mL of anhydrous ethanol, and the solution mixture was continuously stirred to ensure complete dissolution of the components. Then the obtained solution was transferred to a water bath system, kept at 80 °C, and the solvent was gradually evaporated by continuous stirring. The dried solid material was then heat treated at 550 °C in an air environment for 2 h, with a heating rate of 5 °C / min during heat treatment. After natural cooling, a nitrogen vacancy-containing carbon nitride (NvCN) photocatalyst was obtained, hereinafter referred to as NvCN.

[0042] 50 mg of NvCN was dispersed in 5 mL of polyvinylidene fluoride (PVDF, 30 g / L) containing N-methyl-2-pyrrolidone (NMP) solution, and ultrasonically treated for 30 min; then, the obtained mixed solution was uniformly coated on the surface of the carbonized layer with a pipette, and dried in a vacuum oven at 80 °C for 12 h to obtain a photo-thermal evaporation-photocatalytic hydrogen production composite material, denoted as NvCN-CW.

[0043] Example 2 like Figure 3 As shown, the original untreated natural wood exhibits a hydrophilic surface with a contact angle of 73.59°; as the wood surface carbonizes, the contact angle increases to 82.71°; after further loading NvCN on top of the carbonized wood, the contact angle increases to 126.07°; this result indicates that the wood surface changes from hydrophilic to hydrophobic. The wood substrate, based on its hydrophilicity, promotes the absorption and transport of moisture to the uppermost layer through capillary action; while after the NvCN catalyst is loaded, the upper surface of the NvCN-CW changes from hydrophilic to hydrophobic, which is beneficial for the photothermal release of water vapor and accelerates the process of water splitting to produce hydrogen.

[0044] The microstructures of raw, untreated natural wood, pretreated wood (W), NvCN-CW, and NvCN-CW (5-pore) were observed using scanning electron microscopy (SEM). SEM images of raw, untreated natural wood were compared with those of raw, untreated natural wood. Figure 4 Compared to (a), the number of burrs on the wood surface was reduced after soaking in cellulose solvent (a). Figure 4 (b) provides more growth surface for the catalyst. Meanwhile, from Figure 4 As can be observed in (c), the NvCN catalyst is uniformly coated on the wood surface without forming flakes that would clog the pores and affect water transport. Furthermore, EDS analysis (4 in (d)) shows that C, N, O, and F are uniformly distributed on the wood surface, indicating that the NvCN catalyst and PVDF binder have adhered evenly to the wood surface. Finally, the NvCN-CW (5-pore) surface was observed; the interface between the catalyst layer and the carbonized wood substrate was distinct, and the coating area boundaries were clear and complete, indicating that the catalyst loading position was precisely controlled during the preparation process, and no overflow occurred into non-carbonized areas.

[0045] The absorption capacity of each material to the solar spectrum was evaluated using ultraviolet-visible diffuse reflectance spectroscopy (UV-Vis DRS). Figure 5 The results show that, compared with NvCN, NvCN-CW extends the absorption wavelength of the solar spectrum to the visible and near-infrared regions; thanks to the excellent light absorption performance of the carbide layer, NvCN-CW can make great use of sunlight and improve the photothermal effect.

[0046] Example 3 In most existing studies, photocatalytic hydrogen production typically takes place in deionized water systems. However, for natural seawater containing complex ionic compositions, metal ions may not only participate in H+ ionization but also... +competitive reduction reactions, and also deposit or induce corrosion on the catalyst surface, thus significantly reducing the photocatalytic activity. In contrast, NvCN-CW achieves a synergistic hydrogen production by photo-thermal and photocatalytic processes at the gas-solid interface formed by water vapor-photocatalytic hydrogen production catalysts. This photo-thermal evaporation-photocatalytic hydrogen production composite material converts liquid seawater into water vapor through a photo-thermal evaporation process, and the water vapor as a reaction raw material participates in the hydrogen production reaction on the surface of the photocatalytic hydrogen production catalyst. Since the metal ions in seawater lose the carrier in the vaporization process and no longer migrate to the surface of the catalyst with water vapor, the accumulation and coverage of metal ions on the catalyst are effectively avoided, preventing the active sites from being shielded and the loss of photo-generated carriers. At the same time, the gas phase environment reduces the contact opportunities between metal ions and H + .

[0047] Based on the above analysis, photocatalytic hydrogen production of different materials was studied. First, the photocatalytic hydrogen production of pure CW was studied, as shown in Figure 6 , CW only acts as a photo-thermal base material and has no photocatalytic activity. On this basis, the loading amount of NvCN was optimized (a in Figure 7 ). The results show that when the catalyst loading amount is about 30 mg, the photocatalytic hydrogen production rate of NvCN-CW reaches 23.01 mmol m -2 h -1 , which is 1.8 times that of the traditional three-phase NvCN powder system (11.72 mmol m -2 h -1 ).

[0048] As shown in (c) in Figure 7 , the photocatalytic hydrogen production stability of four cycles shows that NvCN-CW has good photocatalytic stability. At the same time, under dark conditions, the hydrogen production rate of NvCN-CW is 0 mmol m -2 h -1 ( Figure 8 ), indicating that the hydrogen production of NvCN-CW needs to be started under light conditions.

[0049] In addition, the hydrogen production performance of NvCN-CW under different spectral conditions was systematically studied (d in Figure 7 ). The results show that the hydrogen production rate of the system is the highest under 300 W xenon lamp irradiation; under simulated sunlight conditions (300 W xenon lamp, AM 1.5G), the hydrogen production rate decreases slightly to 21.05 mmol m -2 h -1 , and under 420 nm monochromatic light irradiation, it further decreases to 15.12 mmol m -2 h -1This indicates that NvCN-CW also has a good hydrogen production rate in the wavelength range of simulated sunlight. All the above results show that this gas-solid two-phase reaction system can convert visible light into heat energy through the photo-thermal effect, greatly improving the hydrogen production efficiency, and using the full spectrum of solar energy to produce hydrogen; in other words, NvCN-CW can efficiently utilize solar energy.

[0050] To further explore the internal factors that the hydrogen production performance of the gas-solid two-phase photocatalytic system induced by photo-thermal is better than that of the traditional powder three-phase photocatalytic system, the reaction thermodynamics, energy transfer and mass transfer in the photocatalytic process were comprehensively evaluated.

[0051] From the perspective of reaction thermodynamics, the reduction potential required for water vapor decomposition can be calculated by the standard free energy of formation (ΔG f ) between water vapor and liquid water: Equation (1); Equation (2); Equation (3); where n is the number of electrons in the reaction, and F is the Faraday constant (F = 96485 C mol -1 ). As shown in Equations (1) and (2), the ΔG f of water vapor decomposition and liquid water are calculated as -228.59 kJ mol -1 and -237.18 kJ mol -1 , respectively. According to Equation (3), the corresponding water decomposition potentials of liquid water and water vapor are E[H2O(l)] = 1.229 V and E[H2O(g)] = 1.185 V, respectively. Therefore, the water decomposition potential of liquid water in the three-phase system is 44 mV higher than that of water vapor in the gas-solid two-phase reaction system, as shown in (a) of Figure 9 Further verification of this conclusion is shown in (b) of Figure 9 When the catalyst is located at the gas-liquid interface or suspended in the air, the hydrogen production rate with water vapor as the main reactant reaches 23.01 mmol m -2 h -1 and 19.07 mmol m -2 h -1 , respectively, which is significantly higher than that when the catalyst is located below the water surface (8.67 mmol m -2 h -1 ) and completely immersed in liquid water (6.64 mmol m -2 h -1The results show that the reaction system in the gas phase exhibits superior hydrogen production kinetics. In contrast, catalysts in the liquid phase are often limited by higher reaction energy barriers, making it difficult to fully realize their reactivity.

[0052] From an energy flow perspective, in traditional three-phase photocatalytic systems, the efficiency of converting solar energy into chemical energy is very low, with most energy lost as heat and phonon energy. First, before solar energy reaches the photocatalyst surface, some near-infrared radiation is absorbed by the reaction medium and lost as waste heat; second, some is lost due to water scattering. During photocatalysis, solar energy can be used for hydrogen production through light absorption and photothermal conversion, but some is also lost as carrier recombination and phonons. In a gas-solid two-phase photocatalytic system, solar energy can directly reach the photocatalyst surface; part is captured by the photothermal material and converted into heat for water evaporation, while the other part is absorbed by the photocatalyst for the photocatalytic process; simultaneously, the increased temperature of the reaction system due to the photothermal effect can improve photocatalytic performance. Figure 10 As shown in (a), when NvCN powder is placed in a hot water environment at the same temperature as the photothermal surface, the photocatalytic hydrogen production rate of NvCN powder is approximately 18.22 mmol m -2 h -1 This is far higher than the hydrogen production rate of NvCN at room temperature.

[0053] also, Figure 7 As shown in (b), the hydrogen production rate of NvCN-CW is 23.01 mmol m -2 h -1 The hydrogen production rate is significantly higher than that of NvCN-W (14.83 mmol m). -2 h -1 This is because high-temperature carbonization treatment creates a connected graphite phase structure within the wood. This graphite phase not only significantly improves the material's electrical conductivity and promotes the rapid separation and transport of photogenerated charge carriers, but also effectively suppresses electron-hole recombination, thereby improving light energy utilization efficiency. Related performance tests were conducted experimentally, such as transient photocurrent (TPC) and electrochemical impedance spectroscopy (EIS). The charge transfer kinetics on the material surface were evaluated using EIS. Typically, the charge carrier transfer resistance is proportional to the arc size. Figure 10 As shown in (b), the original untreated natural wood exhibits the largest arc radius, indicating that it has the greatest resistance to charge transfer; after carbonization and coating with NvCN, the radius is significantly reduced, indicating that the material has higher charge transfer efficiency and lower charge recombination probability due to the presence of the carbonization layer. Figure 10As shown in FIG. 2(c), the transient photocurrent curves of NvCN-CW and NvCN-W samples both exhibit sensitive and stable characteristics under visible light irradiation. Compared with NvCN-W, the photocurrent intensity of NvCN-CW is improved, which indicates that the separation efficiency of photo-generated electrons comes from the carbonized layer. In addition, the response signal of NvCN-CW is more significant, and the photocurrent density is almost twice that of NvCN-W. It is proved that the presence of the carbonized layer reduces the interface reaction resistance and optimizes the separation and transfer of electrons and holes, thereby increasing the amount of hydrogen generation through photocatalysis.

[0054] From the perspective of mass flow, the interface reaction on the surface of the photocatalyst depends on the transfer rate of the reactants from the liquid phase body through the boundary layer and the desorption rate of gaseous products. The bubbles dispersed on the surface of the catalyst and the reaction medium in the traditional three-phase system will weaken the light irradiation intensity due to their scattering and reflection characteristics, and affect the light absorption of the photocatalyst. At the same time, the bubbles generated on the surface of the catalyst will be affected by the adsorption of the catalyst and the pressure of the surrounding liquid phase system. If it cannot be desorbed from the catalyst surface to the external system in time, it will affect the adsorption of the photocatalyst and water molecules, thereby reducing the photocatalytic hydrogen production rate. The gas-solid two-phase system uses water vapor as raw material to carbonize the solid surface of the catalyst active site, thereby getting rid of the defects of the liquid reaction environment. When the composite catalyst NvCN-CW floats on the surface of the liquid, it exhibits the best hydrogen production performance. In addition, experiments on the composite catalyst NvCN-CW in water at different positions Figure 9 (b) in the middle, it is found that the hydrogen production performance of the suspended and floating in water is similar, but after sinking in water, the hydrogen production rate is greatly reduced, and the deeper the water, the lower the hydrogen production rate. This further verifies that the gas-solid two-phase interface not only facilitates the continuous supply of water vapor, but also significantly reduces the adhesion and light shielding effect of bubbles on the catalyst surface, ensuring the full exposure of light intensity and reaction sites.

[0055] The test of NvCN-CW in real seawater is as follows: Figure 10 As shown in FIG. 2(d), the NvCN-CW composite system still maintains excellent photocatalytic hydrogen production performance in seawater, and the hydrogen production rate reaches 18.94 mmol m -2 h -1 . Further research finds that NvCN-CW not only exhibits excellent anti-ion interference ability in high salinity environment, but also has wide environmental applicability: in spring water and lake water conditions, its hydrogen production rates reach 21.411 mmol m -2 h -1 and 19.173 mmol m -2 h -1 , respectively, indicating that the composite material can work stably in various natural water sources.

[0056] Example 4 From Figure 7 It is observed in (a) and Figure 11 With the increase of photocatalytic hydrogen production catalyst coating quality, the hydrogen production rate shows a trend of first rising and then falling, while the evaporation rate is always falling, indicating that there is an energy competition between the two. To further reveal the relationship between photothermal evaporation and photocatalytic hydrogen production, different pore structures (5 holes, 9 holes, 13 holes) were introduced by controlling the coating area on the carbonized wood surface, and the influence of the pore structure on the evaporation and hydrogen production performance was systematically investigated. The results are shown in Figure 12 (a) and (b) of the specification, with the increase of pore density, the water evaporation rate gradually increases, while the photocatalytic hydrogen production rate shows a downward trend. This result clearly shows that the regulation of pore structure enhances the evaporation while sacrificing part of the catalytic activity, thus causing the reverse trend of “evaporation ↑ – hydrogen ↓”.

[0057] Further infrared thermal imaging results (12 (c)) show that the higher the pore density, the more uniform the temperature distribution on the carbonized wood surface, and the overall temperature rise is significantly enhanced. This shows that after introducing the pore structure, the evaporation surface area is expanded, and the gas diffusion and convection are strengthened, so that more incident light energy is converted into latent heat of evaporation in the form of heat. At the same time, the increase of pore structure means the reduction of catalyst coverage area, and the number of active sites available for photoelectron-hole reaction is correspondingly reduced. Through interface regulation, the redistribution of light energy between “evaporation (latent heat channel)” and “photocatalysis (chemical energy channel)” is formed, thus forming a quantifiable energy competition relationship.

[0058] In the photothermal-photocatalytic coupling system, pore structure is not only a geometric factor for regulating evaporation efficiency, but also a key regulatory dimension for determining the flow direction of light energy. By properly designing the pore density and opening rate, a predictable performance balance between fresh water production and hydrogen production rate can be achieved. This finding not only provides a new perspective for understanding the competition mechanism of photothermal evaporation and photocatalytic reaction, but also provides an operational principle for the structural design of future hydrogen energy-fresh water co-production devices: in water-deficient areas, the pore density can be increased to prioritize fresh water acquisition, while in energy-deficient areas, the pore density can be reduced to maintain high hydrogen production efficiency.

[0059] Example 5 In order to study the performance of seawater desalination, NvCN-CW was subjected to various evaporation tests. As shown in Figure 13 (a), (b) and Figure 11As shown, the evaporation capacity of CW is much higher than that of pure water; with the increase of NvCN mass loading, the evaporation rate of NvCN-CW decreases. When NvCN is coated on the surface of CW, the exposed area of CW inevitably decreases, thus weakening its photothermal conversion performance. In addition, NvCN also slightly affects the water evaporation channels on the surface of CW, reducing the water evaporation performance. However, the evaporation rate of NvCN-CW is still much higher than that of pure water, which indicates that the photothermal conversion effect is enhanced. This photothermally induced NvCN-CW composite combines the photothermal conversion effect of CW and the photocatalytic ability of NvCN.

[0060] In addition, Figure 14 It is demonstrated that carbonization of wood plays an important role in the evaporation process. By comparing carbonized wood with original untreated natural wood, fiber-removed wood, it is found that after removing cellulose, the larger pore size formed is conducive to water transport, but it does not exceed much of the original wood, while after carbonization, the evaporation rate is greatly improved, indicating that the improvement of the evaporation rate mainly comes from the carbonization of the wood surface, which broadens the absorption spectrum of the sun Figure 5 ), and enhances the light-heat conversion ability. At the same time, Figure 13 In (c), it is further verified that the evaporation rate of NvCN-CW is much higher than that of NvCN-W.

[0061] Interestingly, by observing Figure 13 (c) and Figure 14 , it is found that after coating the catalyst on the uncarbonized wood, although its solar absorption capacity is improved, the evaporation rate is similar to that of the wood without coating the catalyst. This indicates that the main role of the photocatalyst in utilizing solar energy is to use solar light to produce hydrogen, rather than to evaporate water. In the dark condition, the evaporation rate of NvCN-CW is only 0.07 kg m -2 h -1 ( Figure 15 ), which has little effect on the solar evaporation rate. In addition, the Fourier transform infrared spectroscopy (FTIR) results show that Figure 16 , the presence of the sacrificial agent triethanolamine (TEOA) is not detected in the condensed water.

[0062] Finally, Figure 13 (d) demonstrates the seawater desalination performance of NvCN-CW under sunlight. In seawater, the evaporation rate of NvCN-CW is 0.91 kg m -2 h -1 . At the same time, the evaporation performance of NvCN-CW in different water bodies is further tested, and it is found that its evaporation rates in spring water and lake water conditions are 1.23 kg m -2 h -1 and 0.94 kg m-2 h -1 , indicating that the material can work stably in a variety of natural water sources and has wide environmental applicability.

[0063] As shown in Figure 17 , the application constructs a composite photocatalytic system of carbonized wood loaded nitrogen vacancy g-C3N4 (NvCN-CW), realizing the solar-driven seawater desalination and hydrogen production collaborative conversion. Compared with traditional powder catalysts, the composite material significantly improves the photocatalytic activity by constructing a gas-solid two-phase reaction system, greatly increases the hydrogen production rate, and exhibits excellent cycle stability under seawater conditions. Experimental characterization and theoretical analysis of the composite material reveal multiple synergistic mechanisms such as light-heat temperature rise, gas-solid interface effect and low reaction threshold of gas-phase water vapor brought by the carbonized wood substrate. Through the regulation of the interface pore structure, it is further found that increasing the pore density can increase the evaporation amount but will weaken the hydrogen production efficiency, and accordingly the design principle of "interface geometry-energy distribution-product selectivity" is put forward, which provides a new idea for the energy distribution between different target products.

[0064] This study provides an effective system design idea for simultaneously obtaining clean hydrogen and fresh water in seawater. Future work can further optimize the interface structure parameters, explore other efficient photocatalyst combinations, and verify the feasibility of the system under actual light conditions, to promote the engineering application of solar seawater collaborative hydrogen production technology.

[0065] The above only describes the preferred embodiments of the present application and is not used to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A photo-thermal evaporation-photocatalytic hydrogen production composite material, characterized in that, It takes the delignified wood as a matrix, performs carbonization treatment on the upper surface of the matrix to obtain a carbonized layer, and then coats a photocatalytic hydrogen production catalyst on the upper surface of the carbonized layer. The photocatalytic hydrogen production catalyst is a nitrogen-vacancy carbon nitride (NvCN) photocatalyst.

2. The photo-thermal evaporation-photo-catalytic hydrogen production composite material of claim 1, wherein, The wood is pine wood. The thickness of the carbonized layer accounts for 5-15% of the wood. Or, the loading of the photocatalytic hydrogen production catalyst is 2-6 mg / cm 2 , preferably 3.3 mg / cm 2 .

3. The photo-thermal evaporation-photo-catalytic hydrogen production composite material of claim 1, wherein, The preparation method of the nitrogen-vacancy carbon nitride (NvCN) photocatalyst comprises the following steps: Dissolve urea and N-(4-cyanophenyl)-glycine in an ethanol aqueous solution, collect the solid after evaporation of the solvent to obtain a precursor; Heat treat the precursor to obtain the nitrogen-vacancy carbon nitride (NvCN) photocatalyst.

4. The photo-thermal evaporation-photo-catalytic hydrogen production composite material of claim 3, wherein, The mass ratio of the urea and N-(4-cyanophenyl)-glycine is 10000: (1-7), preferably 10000:3; Or, the volume ratio of ethanol to water in the ethanol aqueous solution is (4.5-5.5):1, preferably 5:1; Or, the concentration of N-(4-cyanophenyl)-glycine in the ethanol aqueous solution is 0.3-2.3 g / L, preferably 1 g / L.

5. The photo-thermal evaporation-photo-catalytic hydrogen production composite material of claim 3, wherein, The evaporation temperature of the solvent is 75-85 ℃, preferably 80 ℃; Or, the heat treatment temperature is 500-600 ℃, preferably 550 ℃; the heat treatment time is 1.5-2.5 h, preferably 2 h; and the heating rate is 4.5-5.5 ℃ / min, preferably 5 ℃ / min.

6. The method for preparing the photo-thermal evaporation-photo-catalytic hydrogen production composite material according to any one of claims 1-5, characterized in that, Comprise the following steps: (1) immerse the wood in a 4-methylmorpholine N-oxide aqueous solution, and after taking out, wash and dry to obtain delignified wood; (2) perform carbonization treatment on the upper surface of the delignified wood to obtain a carbonized layer, and then coat a photocatalytic hydrogen production catalyst on the upper surface of the carbonized layer; and after drying, obtain the photo-thermal evaporation-photocatalytic hydrogen production composite material.

7. The production method according to claim 6, wherein In step (1), the concentration of the 4-methylmorpholine N-oxide aqueous solution is 20-30 wt%, preferably 25 wt%; Or, in step (1), the temperature for immersing in the 4-methylmorpholine N-oxide aqueous solution is 4-10 ℃, preferably 6 ℃; and the time for immersing in the 4-methylmorpholine N-oxide aqueous solution is 2.5-4 h, preferably 3 h; Or, in step (2), the carbonization treatment method comprises: placing the surface to be carbonized on a stainless steel plate, heating with an alcohol lamp, and then quenching in water; preferably, the heating time is 10-20 min, preferably 15 min.

8. The production method according to claim 6, wherein In step (2), the method for coating the photocatalytic hydrogen production catalyst on the upper surface of the carbonized layer comprises: Dissolve polyvinylidene fluoride in N-methyl-2-pyrrolidone to obtain a mixed solution; Disperse the photocatalytic hydrogen production catalyst in the mixed solution, and then coat it on the upper surface of the carbonized layer; Preferably, in the mixed solution, the concentration of polyvinylidene fluoride is 25-35 g / L, preferably 30 g / L; Preferably, the concentration of the photocatalytic hydrogen production catalyst is 8-12 g / L, preferably 10 g / L.

9. The use of the photo-thermal evaporation-photocatalytic hydrogen production composite material according to any one of claims 1-5 or the photo-thermal evaporation-photocatalytic hydrogen production composite material prepared by the preparation method according to any one of claims 6-8 in photocatalytic hydrogen production from seawater.

10. A method of producing hydrogen from seawater, characterized by, The method comprises the following steps: The photo-thermal evaporation-photocatalytic hydrogen production composite material according to any one of claims 1-5 or the photo-thermal evaporation-photocatalytic hydrogen production composite material prepared by the preparation method according to any one of claims 6-8 is floated on the surface of seawater, and the surface coated with the photocatalytic hydrogen production catalyst faces upward, and hydrogen production is carried out under illumination.

Citation Information

Patent Citations

  • Design of photo-thermal surface water evaporation device based on lanthanum hexaboride nanoparticles

    CN110407273A

  • Gas / solid two-phase interface photocatalytic system for seawater hydrogen production and preparation and use method thereof

    CN112844422A

  • Gas / solid two-phase interface photocatalytic system based on carbonized wood and preparation and use method thereof

    CN112934224A

  • Method for producing hydrogen by direct photo-thermal synergistic catalysis of methanol

    CN112973703A

  • Preparation method and application of carbon nitride-loaded self-floating photo-thermal-photocatalytic hydrogen production material

    CN115487845A

Cited By

  • Hydrogen production method and system by recycling PET waste and wastewater

    CN121872323A